Inovasi Bersih: Pelatihan Pembuatan Sabun Cuci Tangan Ekstrak Sereh Wangi (Citronella) Bersama Karang Taruna IKRIMA Gondangrejo Karanganyar - Septiana Ambarwati; Nur Arifah Hidayati; Hutapea, Henny Parida (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Karang Taruna (IKRIMA) plays an active role in increasing productivity by participating in a training program for making natural antiseptic hand washing soap made from citronella. The choice of citronella as the main ingredient is based on its high economic value and natural properties. Additionally, citronella can inhibit the growth of bacteria, viruses, and fungi, making it an ideal choice for hand hygiene products. IKRIMA members have taken part in a series of comprehensive training regarding the manufacture of antiseptic hand washing soap. This activity includes product manufacturing and packaging practices. IKRIMA can produce hand washing soap that meets the desired quality standards, both in terms of antiseptic effectiveness as well as safety and comfort for users. Making antiseptic hand washing soap is one of the positive activities that encourages IKRIMA members to continue learning and developing. Apart from improving skills and knowledge, this activity also provides economic benefits for them and the surrounding community through the sale of the products produced.